2018
DOI: 10.1051/sicotj/2018018
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for onset of delirium after neck of femur fracture surgery: a prospective observational study

Abstract: Background: Delirium is a common complication after surgery in the elderly that leads to increased length of stay and other adverse outcomes. The aim of this study was to better understand the exact causes of post-operative delirium in patients undergoing surgery for neck of femur (NOF) fractures.Methods: We performed a prospective cohort study of 381 consecutive patients undergoing surgery for NOF fractures at a single institution. Baseline cognitive status and risk factors were recorded on admission. Post-op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
29
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 23 publications
5
29
0
2
Order By: Relevance
“…Although dementia status is a major risk factor for delirium (Davis et al, 2015), the changes in lactate and LGR observed are not explained by existing dementia. The data are consistent with previously demonstrated associations between delirium and increased CSF lactate (Caplan et al, 2010) and hypoxia (Tahir et al, 2018).…”
Section: Acute Cognitive Dysfunction and Deliriumsupporting
confidence: 92%
“…Although dementia status is a major risk factor for delirium (Davis et al, 2015), the changes in lactate and LGR observed are not explained by existing dementia. The data are consistent with previously demonstrated associations between delirium and increased CSF lactate (Caplan et al, 2010) and hypoxia (Tahir et al, 2018).…”
Section: Acute Cognitive Dysfunction and Deliriumsupporting
confidence: 92%
“…S3). The data are consistent with previously reported increases in CSF lactate in patients with delirium (43) and with the observation that hypoxia is a risk factor for developing delirium (88,89). Taken collectively, there are several reasons to now focus attention on energy metabolism in delirium.…”
Section: Acute Cognitive Dysfunction and Deliriumsupporting
confidence: 91%
“…Perioperative delirium affects approximately one-third of patients with hip fractures 4 and has been associated with longer inpatient stays and higher 1-year mortality rates. 5 Hip fracture patients with prediagnosed dementia have been shown to be significantly more likely to develop delirium postoperatively. 5 Thus, in 2012, the British Orthopaedic Association Standards for Trauma and Orthopaedics (BOAST) guidelines stated that one should "Assess patient's risk of delirium or dementia by actively looking for cognitive impairment when patients first present with hip fracture and perform regular reassessment."…”
Section: Introductionmentioning
confidence: 99%
“…5 Hip fracture patients with prediagnosed dementia have been shown to be significantly more likely to develop delirium postoperatively. 5 Thus, in 2012, the British Orthopaedic Association Standards for Trauma and Orthopaedics (BOAST) guidelines stated that one should "Assess patient's risk of delirium or dementia by actively looking for cognitive impairment when patients first present with hip fracture and perform regular reassessment." 6 More recently, the British Orthopaedic Association extended their guidelines beyond hip fractures, stating that all elderly or frail orthopedic trauma patients should routinely be assessed using a validated delirium assessment tool such as the 4AT.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation